Subcluster AZ1 Annotation Report - Beyer, Andrea; Bouklas, Tejas; Dojs, Madeline; Edgington, Nicholas; Harrison, Melinda; Rudner, Adam; Swerdlow, Sarah; Delesalle, Veronique; Page, Shallee (QUBES, 2025)
This report describes features of actinobacteriophages assigned to subcluster AZ1. Additional phages may have been added to the phagesDB database since the generation of this report.
Keywords: Annotation; DNA; Genome; Genomics; Human genome; Selection (genetic algorithm); dept.bio

Cluster M mycobacteriophages Bongo, PegLeg, and Rey with unusually large repertoires of tRNA isotypes - Pope, Welkin H; Anders, Kirk R; Baird, Madison A; Bowman, Charles A; Boyle, Michelle M; Broussard, Gregory W; Chow, Tiffany W; Clase, Kari; Cooper, Shannon D; Cornely, Kathleen; Dejong, Randall J; Delesalle, Veronique A; et al. (Journal of Virology, 2014)
Genomic analysis of a large set of phages infecting the common host Mycobacterium smegmatis mc2155 shows that they span considerable genetic diversity. There are more than 20 distinct types that lack nucleotide similarity with each other, and there is considerable diversity within most of the groups. Three newly isolated temperate mycobacteriophages, Bongo, PegLeg, and Rey, constitute a new group (cluster M), with the closely related phages Bongo and PegLeg forming subcluster M1 and the more distantly related Rey forming subcluster M2. The clusterMmycobacteriophages have siphoviral morphologies with unusually long tails, are homoimmune, and have larger than average genomes (80.2 to 83.7 kbp). They exhibit a variety of features not previously described in other mycobacteriophages, including noncanonical genome architectures and several unusual sets of conserved repeated sequences suggesting novel regulatory systems for both transcription and translation. In addition to containing transfer-messenger RNA and RtcB-like RNA ligase genes, their genomes encode 21 to 24 tRNA genes encompassing complete or nearly complete sets of isotypes. We predict that these tRNAs are used in late lytic growth, likely compensating for the degradation or inadequacy of host tRNAs. They may represent a complete set of tRNAs necessary for late lytic growth, especially when taken together with the apparent lack of codons in the same late genes that correspond to tRNAs that the genomes of the phages do not obviously encode. © 2014, American Society for Microbiology.
40 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-261-678-659-153 tex.type: [object Object]
Keywords: Base Composition; Base Sequence; Codon; Conserved Sequence; DNA binding motif; DNA sequence; Gene Order; Genome Size; Genome; Viral; Inverted Repeat Sequences; Lysogeny; Multigene Family; Mycobacteriophages; Mycobacterium smegmatis; Open Reading Frames; Phylogeny; RNA cleavage; RNA degradation; RNA translation; RNA; Transfer; RNA; Viral; Repetitive Sequences; Nucleic Acid; Sequence Alignment; Virion; Virus Assembly; article; controlled study; dept.bio; gene cassette; gene control; gene structure; genetic analysis; genetic transcription; genetic variability; membrane protein; mycobacteriophage; mycobacteriophage Bongo; mycobacteriophage M; mycobacteriophage Pegleg; mycobacteriophage Rey; nonhuman; nucleotide sequence; priority journal; protein gp19; protein gp23; protein gp24; protein gp26; protein gp30; protein gp31; protein gp39; single stranded DNA binding protein; tmp gene; transfer RNA; unclassified drug; viral genetics; virus assembly; virus classification; virus immunity; virus morphology